Pengaruh Opini Audit, Pergantian Manajemen dan Financial Distress terhadap Auditor Switching - Rozita Azlin; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2023)
The purpose of this study was to analyze the effect of audit opinion, management change and financial distress on auditor switching. The data use in this study an annual and financial reports in infrastructure, utilities and transport companies listed on the Indonesia Stock Exchange (IDX) in the period 2015-2021. The method of taking data samples using purposive sampling method. The data analysis method used is logistic regression analysis. The results of the research concluded that audit opinion have significant relationship with auditor switching while management change and financial distress does not have a significant relationship with auditor switching. The next researcher can consider using other variables such as audit reputation, fee audit and audit delay and other variables that might influence auditor switching.